2021
DOI: 10.2147/jir.s335061
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis is Involved in Hyperoxic Lung Injury in Neonatal Rats

Abstract: Purpose: To evaluate whether ferroptosis is involved in hyperoxic acute lung injury (HALI) and its mechanisms through the HALI model. Methods: HE staining was used to assess lung injury pathology after the establishment of neonatal rat HALI model. ELISA was used to detect ROS, GPX4, and GSH expression. Prussian blue staining and Western Blot were used to detect iron deposition and the expression of ferroptosis-related proteins, respectively. Results: The HALI group showed pathological changes with larger and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…These studies suggested that rGSH served a protective role for the body through its redox function. in the present study, rGSH reduced the level of iron ions and acSl4 in aKi, and increased the expression of GPX4, thereby reducing the degree of kidney damage, which demonstrated that rGSH could ameliorate hemolytic aKi via regulation of the ferroptosis pathway, which was consistent with the results of previous studies that rGSH affects ferroptosis via regulation of the ferroptosis-related gene GPX4 (30). in the in vitro experiments, construction of the HK-2 cell ferroptosis model demonstrated that RGSH could significantly increase cell viability and significantly increase the lipid oxide level in cells, which inhibited cell apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…These studies suggested that rGSH served a protective role for the body through its redox function. in the present study, rGSH reduced the level of iron ions and acSl4 in aKi, and increased the expression of GPX4, thereby reducing the degree of kidney damage, which demonstrated that rGSH could ameliorate hemolytic aKi via regulation of the ferroptosis pathway, which was consistent with the results of previous studies that rGSH affects ferroptosis via regulation of the ferroptosis-related gene GPX4 (30). in the in vitro experiments, construction of the HK-2 cell ferroptosis model demonstrated that RGSH could significantly increase cell viability and significantly increase the lipid oxide level in cells, which inhibited cell apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Ferroptosis is a newly discovered form of cell death caused by the accumulation of iron-dependent lipid peroxides (LPOs) [51][52][53] that has recently been associated with immune responses in tumors. [54][55][56] Several studies have even described ferroptosis cell death as a form of ICD.…”
Section: Ferroptosismentioning
confidence: 99%
“…Next, we would like to explore the effects of the FHOD1‐HSPB1 signaling axis in the regulation of ferroptosis. As shown in Figure 5A, in T98G and U251 glioma cells, HSPB1 overexpression suppressed the FHOD1 knockdown‐mediated upregulation of TRF1, a ferroptosis‐positive regulator 34 . Moreover, overexpression of HSPB1 in FHOD1‐depleted glioma cells significantly reduced the inhibition of cell growth (Figure 5B,C).…”
Section: Resultsmentioning
confidence: 83%